PROFIL PENYIMPANAN VAKSIN COVID-19 DI SELURUH PUSKESMAS KOTA BUKITTINGGI - Mega Yulia; Luthfi, Fakhri; Armal, Khairil (Poltekkes Kemenkes Bengkulu, 2023)
Bukittinggi is a city in the province of West Sumatera with a population of 121,028 people. From this large population, it is predicted that the need for vaccines is very large. For this reason, the role of health service facilities in terms of handling vaccines is urgently needed, especially in terms of vaccine storage so that vaccine quality can be maintained. This research is a descriptive study using a checklist which aims to find out whether the storage of the covid-19 vaccine in Bukittinggi City complies with the standards for storing the covid-19 vaccine. From the research conducted, it can be concluded that the suitability of the requirements for facilities and infrastructure is categorized as very good for all Puskesmas in Bukittinggi City with a percentage range of 86.66% -93.33%. Sari, Mandiangin Health Center, Plus Mandiangin Health Center, Gulai Bancah Health Center and Tigo Baleh Health Center with a percentage range of 89.47% -84.21%. The Guguk Panjang Health Center is categorized as good with a percentage of 78.94%. Meanwhile, the suitability of vaccine management requirements is categorized as very good for all health centers in Bukittinggi City with a percentage range of 92.85% -100%.